Gambaran Status Gizi Pasien Diabetes Melitus Tipe 2 Berdasarkan Antropometri - Mukhyarjon, Mukhyarjon; Pardede, Imelda Tresia; Putri, Wulan Amelia (Jurnal Ilmu Kedokteran, 2021)
Nutritional status is an expression of a state of balance between intake of nutrient and their requirements. Diabetes mellitus is one of the comorbid diseases of obesity due to insulin resistance. This has a negative impact on the tissue causing complications, especially central obesity because it is more resistant to the effects of insulin than adipocytes in other areas. This study aims to describe the nutritional status of people with type 2 diabetes based on anthropometry. This research was a descriptive study with a cross sectional approach using purposive sampling method on 62 respondents. The data collected were anthropometric examinations, HbA1c, and questionnaires. Result of this study showed that most subjects were aged between 45-65 years (64,5%), mostly female (54,8%). Most subject (75,8%) being diabetic ≤5 years and as many as 61,3% had HbA1c levels ≥7%. The most prevalent diabetic drag used was metformin (69,4%). From the anthropometric examination, it was found that the most nutritional status was obesity (54.85%), with the most age> 45 years (56.9%), male gender (57.1%), onset from type 2 diabetes >65 years ( 66,7%), HbA1c levels ≥7% (55.3%) and use of insulin with a percentage of 71,4%. As many as 72,6% subject had central obesity.